The Influence of Local Government Integrity on Local Government Budget and its Implications for Development - Indra Jaya (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to analyze the influence of local government integrity on APBD management and its implications for the quality of regional development in Indonesia. Secondary data from BPS, SPI, and APBD records for cities and regencies in Indonesia in 2022 were used. Data were analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. This method integrates measurement models to validate indicators and structural models to assess relationships between latent variables. Key evaluation criteria, including reliability, validity, and hypothesis testing, were employed to ensure robustness. The results indicate that higher local government integrity improves APBD management, albeit with a relatively modest effect. Integrity plays a crucial role in preventing corruption and enhancing the sustainability of regional development, highlighting its importance in public financial management. These findings underscore the necessity of promoting high-integrity practices in local governance to achieve sustainable development goals.